Lack of association between mutation in IL36RN and palmoplantar pustular psoriasis in Chinese patients, - Yu Xiaoling; Shu Dan; Jin Hongzhong (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Palmoplantar pustulosis is considered to be a localized pustular psoriasis confined to the palms and soles. Mutation of the IL36RN gene, encoding interleukin-36 receptor antagonist (IL-36Ra), is associated with generalized pustular psoriasis, but IL36RN mutations in Chinese palmoplantar pustulosis patients have not previously been investigated. Objective: The aim of this study was to evaluate the mutation of IL36RN in Chinese patients with palmoplantar pustulosis. Methods: Fifty-one Han Chinese patients with palmoplantar pustulosis were recruited. All exons and exon-intron boundary sequences of IL36RN were amplified in polymerase chain reactions, and Sanger sequencing of the amplicons was performed. Results: Among the 51 palmoplantar pustulosis patients, four different single-base substitutions were identified in nine patients. The mutations were c.140A>G/p.Asn47Ser in five patients, c.258G>A/p.Met86IIe in two patients, and c.115+6T>C and c.169G>A/p.Val57IIe in one patient each. All mutations were heterozygous. Comparison with the human genome database and reported literature suggested that these variants may not be pathogenic mutations causing palmoplantar pustulosis. Furthermore, there was no difference in disease severity, onset age, or disease duration between patients with these heterozygous IL36RN variants and those without (p > 0.1). Study limitation: Lack of the further evaluation of IL36Ra protein in palmoplantar pustulosis lesions. Conclusions: The four variants of IL36RN identified did not appear to be associated with the specific phenotypes of palmoplantar pustulosis.